The measurement of post-acquisition performance in RSA using economic value added (EVA) - Makhele, Amos Tlali (My University, 2014)
This study re-examines post-acquisition performance of acquiring firms in South Africa using Economic Value Add (EVA). Investigation of the 336 acquisitions occurring during 2000 to 2011 reveals that acquiring firms experience significantly deteriorating EVA after the completion of acquisitions. Further, this study evaluates the performance of other traditional accounting measures including Earning per share (EPS), Return on capital (ROC), Return of Assets (ROA) and Return on Equity (ROE) post acquisition. The results suggest that acquiring firms tend to experience slightly improved performance after completion of the acquisitions when using traditional accounting measures. But the improved operating performance is wiped out by capital costs of the large premiums paid to the target firm, creating no real economic gains to the acquiring firm‘s shareholders
Thesis (M.M. (Finance & Investment))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2013.
Keywords: Consolidation and merger of corporations; Corporations; Finance; South Africa